2017
DOI: 10.18632/oncotarget.15826
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DBCCR1 as a suppressor in the development of lung cancer that is associated with increased DNA methyltransferase 1

Abstract: Accumulating evidence has pointed to a role of the CpG island hypermethylation in the regulation of cancer-related genes in tumor progression. However, the biological impacts in cancer pathogenesis associated with down-regulation of such gene targets remains elusive. Here we focused on a potential target of hypermethylation, DBCCR1 (deleted in bladder cancer chromosome region 1), a gene encoding a candidate tumor suppressor. We found that the expression of DBCCR1 is significantly lower in the lung cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…29 For example, DNMT1 promotes tumorigenesis and development of lung cancer by promoting supermethylation of the CpG islands of the cancer suppressor DBCCR1. 30 DNMT1 inhibits PTEN expression in bladder cancer by maintaining the state of CpG methylation in the promoter. 31 It has been reported that DNMT inhibitors can reverse the supermethylation of tumor suppressors and activate their expression, thereby inhibiting the malignant progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…29 For example, DNMT1 promotes tumorigenesis and development of lung cancer by promoting supermethylation of the CpG islands of the cancer suppressor DBCCR1. 30 DNMT1 inhibits PTEN expression in bladder cancer by maintaining the state of CpG methylation in the promoter. 31 It has been reported that DNMT inhibitors can reverse the supermethylation of tumor suppressors and activate their expression, thereby inhibiting the malignant progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have con rmed the effect of CpG island hypermethylation on the regulation of cancerassociated genes in tumorigenesis and progression [17]. For example, the methylation degree of miR-608 was higher in two cancer cells lines compared with normal cell line with the methylation level of 91.4% and 87.3% respectively, and also proposed that CpG islands hypermethylation might cause the silencing of mRNA expression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research indicated that the methylation of cancer suppressor genes was in close relationship with cancer development [26]. Growing evidence showed clearly that the CpG island hypermethylation in oncogenes played a fundamental role in the process of colon cancer development [27, 28]. Previous studies have showed that HOXD10 which was aberrantly hypermethylated in papillary thyroid cancer may act as a tumor suppressor [29].…”
Section: Discussionmentioning
confidence: 99%